ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBERIAN KREDIT MIKRO DAN KETERKAITANNYA DENGAN KINERJA PT BANK MANDIRI (PERSERO) TBK UNIT KERJA CLUSTER PALEMBANG ARIEF-2 PROVINSI BENGKULU - Fitriano, Yun; Fachruzzaman, Fachruzzaman; Baihaqi, Baihaqi (JURNAL FAIRNESS, 2013)
This research aim to examine if there is or not the influence of the length of business, business capacity, the characteristic of debtor, economy sector which is paid, and the target of performance that is specified by management to the micro credit decision which taken by the Analyst of Micro Credit (MKA) and Manager of Micro Mandiri (MMM) of Mandiri Bank. This research take place in Mandiri Bank work unit Palembang Cluster Arief-2 Bengkulu Province which consist of 17 units of the business partner mandiri/micro branch office. The sample in this research is all of Analyst of Micro Credit (MKA) and the Manager of Micro Credit Palembang (MMM) Cluster Arief-2 Bengkulu Province. The collected data is primer data from the spread of questionnaire then processed by multiple regression examine analyst. The result of this research show that simultaneously the variable of length of business, business capacity, characteristic of debtor, the economic sector which is paid and the target of performance that is specified by management having an effect on micro credit decision. Partially, the length of business variable influence the micro credit decision while other variables do not influence. The result of this research also give an empirical evidence that the main factor which most given attention by the analyst of Micro Credit (MKA) and the Manager of Micro Credit (MMM) of the Mandiri Bank in deciding micro credit is the length of business factor and empirically is proven in this research, by paying attention on the length of business the collectible performance is fluent Palembang Cluster Arief-2 Bengkulu Province can be high with the low number of non performing loan.